Standard methods for the examination of water and wastewater / prepared and published jointly by American Public Health Association, American Water Works Association, Water Environment Federation ; joint editorial board, Eugene W. Rice ... [et al.] ; managing editor, Laura Bridgewater. - Rice, Eugene W.; Bridgewater, Laura; American Public Health Association; American Water Works Association; Water Environment Federation (Washington, D.C. : American Public Health Association, 2012)
'The signature undertaking of the Twenty-Second Edition was clarifying the QC practices necessary to perform the methods in this manual. Section in Part 1000 were rewritten, and detailed QC sections were added in Parts 2000 through 7000. These changes are a direct and necessary result of the mandate to stay abreast of regulatory requirements and a policy intended to clarify the QC steps considered to be an integral part of each test method. Additional QC steps were added to almost half of the sections.'--pref. p. iv.
Includes bibliographical references and index.
Keywords: Water -- Analysis; Sewage -- Analysis; Water -- analysis